Community Awareness and Participation in Handling Covid-19 in Surabaya, Indonesia - Wiwi Wikanta1 , Sukadiono2 , Abdul Aziz Alimul Hidayat3 , Sujnah4 , dan Hetty Murdiyani5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study aimed to determine the level of public awareness and participation in handling Covid-19 inSurabaya, Indonesia. Surabaya was one of the second cities with the largest covid-19 events in Indonesia,after Jakarta. This research used survey method. The sample was determined by the simple randomsampling method. The sample size in this study was 251 respondents. Research data were collected usinga questionnaire, and analyzed with descriptive analysis. The results showed: an average awareness valueof 3.43 (very high) and participation of 1.72 (very high), high business initiatives by 55%, a correlationvalue between awareness and participation of 0.25 included in the weak category. The results of this studycan provide significant benefits in the disciplines of education and health psychology. The mayors canuse the findings in this study to overcome the problem of Covid-19 in the community. It turns out that toreduce the spread of covid-19 is not only enough to do with health education, but increasing awareness andparticipation in the community is very important and significant in overcoming the spread of covid-19 dueto lack of awareness in the application of physical and social distancing, the use of masks, hand washing